Ireland : 2016 Article IV Consultation and Fifth Post-Program Monitoring-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the rebound of the Irish economy has been exceptional. High frequency indicators suggest that growth momentum has continued in 2016. Solid job creation has reduced the unemployment rate below 8 percent. Inflation has hovered around zero as low commodity and food prices more than offset rising cost of services, particularly housing rents. Taking into account negative spillovers, real GDP growth is projected to decline to just below 5 percent in 2016 and converge to its estimated potential over the medium-term on the back of more moderate export growth and investment activity.